Analisis Faktor yang Mempengaruhi Minat Kegiatan Kepramukaan Siswa di SDN 1 Bakan - Haslindatul Akmi (Journal of Elementary Education Research, 2025)
Scouting (Kepramukaan) is mandated in Indonesia as an essential co-curricular activity for character education, leadership development, and fostering nationalism. The success of this program critically relies on genuine student interest, which can be influenced by both internal (psychological) and external (environmental) factors. Low engagement often reduces the effectiveness of character-building objectives. Therefore, this study aims to specifically identify and analyze the dominant factors influencing student interest at the elementary school level, particularly at SDN 1 Bakan. Using a (Specify: Qualitative/Quantitative) approach, the research investigates the impact of internal factors such as self-motivation, and external factors like the role of the instructors (Pembina), program variety, and parental support. The results of this analysis are crucial for providing practical recommendations to the school and the instructors to optimize the design and execution of the Scouting program, ensuring it is more engaging, relevant, and effective in achieving its goal of holistic student character development.